Use of drains versus no drains after burr-hole evacuation of chronic subdural hematoma. (3rd June 2015) - Moores, M; Fenerty, L; Thibault-Halman, G; Kureshi, N; Walling, S; Clarke, DB
Abstract : Background: Chronic subdural hematomas (cSDH) are a common neurosurgical problem with significant morbidity and mortality. Current treatment methods are variable. Post-operative subdural drain used in conjunction with burr-hole craniostomy may reduce recurrence. This study compared recurrence rates for cSDH between two surgical practices with and without use of post-operative subdural drain at the QEII Health Sciences Center. Methods: A retrospective chart review was conducted to compare recurrence rates between surgical patients treated with or without a post-operative drain between 1997- 2012. The primary endpoint was recurrence, defined as occurrence of symptoms due to hematoma confirmed by CT within six months of the original operation. Categorical frequencies were compared with chi square or Fisher's exact test. Logistic regression was performed to identify risk factors for recurrence. Results: There were 85 patients (mean age 73 years; SD 13.0) who had burr-hole craniostomy. Age, cSDH volume, site, GCS, anticoagulation, drain, conservative treatment with steroids and perioperative steroids were not found to be independent predictors of recurrence. Recurrence occurred in 2 of 34 (5.9%) patients with drain, and in 7 of 51 (13.7%) without (p=0.305). There were insufficient data to compare mortality and complications. Conclusions: Use of post-operative subdural drain did not significantly alter the cSDH recurrence rate.